Factors affecting delayed tooth eruption among children aged 6-24 Months: a cross-sectional study - Umniyati, Helwiah; Prasonto, Djuned; Pramigi, Ufo; Suriyah, Wastuti Hidayati; Mohd Dom, Tuti Ningseh (Fakultas Kedokteran Gigi Universitas Padjadjaran, 2025)
Introduction: Nutritional status is one of the most important things that parents must pay attention to, especially when the child is in the golden period of growth, which consists of the period of growth and development, including tooth eruption. Tooth eruption is influenced by various factors, one of which is nutritional factors. Mothers' health status may then determine their children's primary dentition status, and also the child's status itself. This study aims to analyze factors related to delayed tooth eruption in children aged 6–24 months. Methods: This research was a cross-sectional study conducted among 464 children aged 6–24 months. The sampling method employed was a total sampling technique undertaken in 10 villages within the Pandeglang district, West Java. Tooth eruption time used the Primary Tooth Development figure by the American Dental Association (ADA). Statistical analysis was performed using chi-square and logistic regression. Research ethics were obtained from YARSI University. Results: There was a significant relationship between delayed tooth eruption and mother’s Body Mass Index (BMI), nutritional status of children, and gender, with a value of ρ<0.05. Female sex (AOR=1.51), stunting (AOR=1.86), and underweight (AOR=1.78) increased the odds of delayed eruption. Conclusion: Nutritional status influences eruption timing. Integrating oral assessments into routine child growth monitoring could improve early detection of developmental risks in children aged 6 – 24 months. Faktor-faktor yang mempengaruhi keterlambatan erupsi gigi pada anak usia 6-24 bulan: studi cross-sectionalPendahuluan: Status gizi merupakan faktor krusial yang perlu diperhatikan oleh orang tua, terutama pada masa perkembangan awal anak, yang meliputi periode pertumbuhan pesat, perkembangan fisiologis, serta erupsi gigi. Erupsi gigi dipengaruhi oleh berbagai faktor, salah satunya adalah faktor gizi. Status kesehatan ibu menentukan status gigi sulung anak-anak mereka, demikian pula status anak itu sendiri. Penelitian ini bertujuan untuk menganalisis faktor-faktor yang berhubungan dengan keterlambatan erupsi gigi pada anak usia 6 - 24 bulan. Metode: Penelitian ini merupakan penelitian potong lintang yang dilakukan di antara 464 anak usia 6 - 24 bulan. Metode pengambilan sampel yang digunakan adalah teknik total sampling yang dilakukan di 10 desa di kabupaten Pandeglang, Jawa Barat. Waktu erupsi gigi menggunakan angka Perkembangan Gigi Sulung oleh American Dental Association (ADA). Analisis statistik dilakukan dengan menggunakan chi-square dan regresi logistik. Hasil: Terdapat hubungan yang signifikan antara keterlambatan erupsi gigi dengan IMT ibu, status gizi anak, dan jenis kelamin, diperoleh nilai p=0,05. Jenis kelamin perempuan (AOR=1,51), stunting (AOR=1,86), dan berat badan kurang (AOR=1,78) meningkatkan kemungkinan erupsi tertunda. Simpulan: Status gizi secara memengaruhi waktu erupsi. Mengintegrasikan pemeriksaan gigi ke dalam pemantauan pertumbuhan anak secara rutin dapat meningkatkan deteksi dini risiko pada anak usia 6-24 bulan.